2022
DOI: 10.3390/agronomy12051204
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus Field Growth and Colonization of Clones Pre-Inoculated with Ectomycorrhizal Fungi

Abstract: Ectomycorrhizae are classified as biotechnology to increase the sustainability of planted forests, and fieldwork is needed to confirm its effectiveness. The growth of rooted cuttings of Eucalyptus clones GG100 and GG680, which had been previously inoculated in the nursery with ectomycorrhizal fungi, was evaluated after planting them in the field. The ectomycorrhizal fungi (EMF) inoculated were: Pisolithus microcarpus, Hysterangium gardneri, or Scleroderma areolatum. Uninoculated rooted cuttings were used as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Plants may improve their competitive ability because of these immediate benefits. Plant height, fresh and dry weight of shoot, and root of Cenchrus ciliaris increased the most in rhizospheric soils of Saccharum bengalense, compared to other treatments, possibly due to the favorable response of mycorrhizal inoculation under the moderate fertility state of the soil [2,3]. This is consistent with previous findings, which indicated that mycorrhizal inoculation raised the weight of plant roots and shoots substantially.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Plants may improve their competitive ability because of these immediate benefits. Plant height, fresh and dry weight of shoot, and root of Cenchrus ciliaris increased the most in rhizospheric soils of Saccharum bengalense, compared to other treatments, possibly due to the favorable response of mycorrhizal inoculation under the moderate fertility state of the soil [2,3]. This is consistent with previous findings, which indicated that mycorrhizal inoculation raised the weight of plant roots and shoots substantially.…”
Section: Discussionsupporting
confidence: 91%
“…Two types of mycorrhizal associations are known as ecto-and endo-mycorrhiza. The 2 of 18 ecto-mycorrhiza is characterized by an extracellular fungal growth in the root cortex [2,3]. Boreal forest trees have more than 5000 species, mainly of the Basidiomycetes variety, and are more common in the temperate zone [4].…”
Section: Introductionmentioning
confidence: 99%